2021
DOI: 10.1038/s41598-020-80474-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a machine learning model for predicting pediatric mortality in the early stages of intensive care unit admission

Abstract: The aim of this study was to develop a predictive model of pediatric mortality in the early stages of intensive care unit (ICU) admission using machine learning. Patients less than 18 years old who were admitted to ICUs at four tertiary referral hospitals were enrolled. Three hospitals were designated as the derivation cohort for machine learning model development and internal validation, and the other hospital was designated as the validation cohort for external validation. We developed a random forest (RF) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…To the best of our knowledge, there is no similar evidence on the pediatric population with HF, even if MLTs have also been primarily used in developing predictive models in critically ill children. For example, several studies used MLTs for early mortality prediction, the development of sepsis, or the need for pediatric intensive care unit transfer for newly hospitalized children [ 33 , 34 , 35 ]. However, no studies have investigated the development of a severe condition such as HF in patients admitted to PICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is no similar evidence on the pediatric population with HF, even if MLTs have also been primarily used in developing predictive models in critically ill children. For example, several studies used MLTs for early mortality prediction, the development of sepsis, or the need for pediatric intensive care unit transfer for newly hospitalized children [ 33 , 34 , 35 ]. However, no studies have investigated the development of a severe condition such as HF in patients admitted to PICU.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that the most important variables in the random forest model have also been shown to be important predictors in prior research in pediatric settings [ 12 ]. Recently, Lee et al developed a machine learning model for predicting pediatric mortality in the early stages of intensive care unit admission and compared it with PIM 3 score [ 33 ]. Interestingly, they found that the random forest model performed better than PIM 3 score in predicting mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the proposed models were developed to make one prediction per patient encounter using data within the first hours after ICU admission (37)(38)(39)(40), rather than predict the risk of mortality continuously across the entire encounter. However, in order to continually assess individual patient's risk of clinical deterioration or mortality it is important to integrate information not only from a single time point, as the current scoring systems do, but also data from previous time points, that is, longitudinal temporal data.…”
Section: Machine Learning To Predict Mortalitymentioning
confidence: 99%
“…Advanced machine learning algorithms offer an ability to engage with complexity and non-linearity that make them an appealing tool for a wide range of new applications such as image recognition with convolutional neural networks (20) and time series analysis with recurrent neural networks (21) and existing applications such as prediction of end-points such as mortality (22). Recently, several studies have reported the use of machine learning approaches with encouraging results (21,(23)(24)(25). To date, the full extent to which machine learning approaches can be applied in pediatric research has not been fully explored, but, as Londsdale et al point out, the opportunities for improving patient care are substantial (26).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks used in supervised classification tasks such as described in this study are referred to as perceptrons. Weights are adjusted through stochastic gradient descent (25).…”
Section: Introductionmentioning
confidence: 99%